MECHANISMS FOR IMPROVING YOUNG PEOPLE IN THE EDUCATION OF THE FAMILY, COMMUNITY AND EDUCATIONAL INSTITUTION - Abirova Umida Nazarovna (Journals Park Publishing, 2022)
The article provides technology and recommendations for the social partnership in the family, community and educational institutions in the article in Uzbekistan. Basic concepts: youth, education, education, family, mahalla, social, social, spirituality, enlightenment.